Penerapan Artificial Intelligence (AI) Terhadap Seorang Penyandang Disabilitas Tunanetra - Mangapul Siahaan; Christopher Harsana Jasa; Kevin Anderson; Satria Lim; Wahyu Yudianto; Melissa Valentino Rosiana (Journal of Information System and Technology (JOINT), 2020)
For a person with visual disabilities, in modern times it is not an obstacle for them to study in order to get good and highest possible insights, therefore an Artificial Intelligence is created or it can be called (Artificial Intelligence). Artificial Intelligence can be said as robots that mimic human behavior, the purpose of Artificial Intelligence is to facilitate an activity or work for humans. One example is (Speech Recognition). Speech Recognition is a process that identifies the sound that comes from the pronunciation of a spoken word, Speech Recognition is a system that can recognize voices from humans and then translate it into data that can be captured by a computer system. Blindness is a general term used for the condition of a human who experiences disturbances or obstacles in the sense of sight. With this Speech Recognition, can make it easier for a person with visual disabilities to do daily activities better.